0429 EVOLUTION OF GRAY MATTER VOLUME IN MILD AND MODERATE OBSTRUCTIVE SLEEP APNEA. (28th April 2017) - L'Heureux, F; Baril, A; Gagnon, K; Bedetti, C; Montplaisir, J; Gosselin, N
Abstract: Introduction: Cerebral gray matter changes were reported in individuals with obstructive sleep apnea (OSA). However, the evolution of these gray matter changes over time is unknown. Considering that over 50% of individuals aged 55 and older who present mild to moderate OSA (apnea-hypopnea index [AHI] between 5 and 30) remain untreated, it is particularly important to better understand the evolution of gray matter changes in this subgroup. Our objective was to investigate the evolution of the gray matter volume in this subgroup using voxel-based morphometry (VBM) and magnetic resonance imaging. Methods: Twelve control subjects (age: 63.8 ± 7.2 yo; AHI: 1.9 ± 1.5) and 18 individuals with untreated mild to moderate OSA (age: 63.9 ± 5.2 yo; AHI: 12.1 ± 6.5) were evaluated twice using a magnetic resonance imaging with an 18-month delay between visits. The VBM method with paired t-tests was used to compare gray matter volumes between visits in each group separately (p<0.05 FWE cluster level). Results: After 18 months, we observed a decreased volume in the caudate nuclei, the right putamen and the globus pallidus in the untreated OSA group. However, the control group showed reduced volume of the right cerebellum and the inferior temporal gyrus after 18 months. Conclusion: Distinct patterns of changes in gray matter volume were observed in the OSA versus the control group. The atrophy found in the control subjects were previously reported with normal aging. Decreased volume in the basal ganglia was specific to the OSA group and could be explained by the chronic exposure to hypoxia, excitotoxicity and changes in regional cerebral blood flow. Our results suggest that even mild or moderate OSA causes gray matter damages different from normal aging over time. Support (If Any):